Moderating Role of Financial Characteristics in Sectoral Performance During the Period of Economic Disruption: Evidence from the Covid-19 Pandemic - Joshi, Himanshu; Joshi, Bhavya (The Indonesian Capital Market Review, 2023)
The exogenous shock of the Covid-19 pandemic disrupted the equity market worldwide, however its impact on the sectoral returns varied. Sectors like aviation, hospitality, and retail were the worst affected because of imposed lockdowns. Contrarily, technology, e-commerce, pharmaceutical, and biotech sectors thrived for the same reasons. The present study evaluates the impact of covid-19 disruption on firms from diverse sectors and examines the moderating effect of firm’s financial characteristics on sectoral performance by establishing a causal relationship between the firm's cumulative abnormal returns generated during the various phases of the pandemic and their sectoral and financial characteristics using data for 317 firms listed on the National Stock Exchange of India. Results indicate that the firm's financial characteristics such as cash holdings, dividends, asset tangibility and analyst coverage moderate the impact of the Covid-19 pandemic on sectoral performance. Findings provide evidence in support of the role of information asymmetry during economic disruptions.